Comparison of Calcium Intake Status by Region and Socioeconomic Status in Korea: The 2011-2013 Korea National Health and Nutrition Examination Survey - Lim, Hee-Sook (J Bone Metab, 2015)
BACKGROUND: Calcium is an essential element nutrient in our body, and insufficient calcium intake is very common in Korean. Socioeconomic status (SES) is known to be associated with quality of diet and health. The purpose of this study was to compare between calcium intake by region and SES. METHODS: This study used data from a nationally represented sample of Koreans (n=19,249) from 2011 to 2013 Korea National Health and Nutrition Examination Survey. We were divided into six regions: Seoul and Gyeonggi-do, Gangwon-do, Chungcheong-do, Jeolla-do, Gyeongsang-do, and Jeju-do. Daily calcium intake and dietary quality based on 24 hr recall data was calculated and analyzed by the sex, age, SES. RESULTS: The regions with the highest calcium intakes in both males and females were Seoul and Gyeonggi-do. The age groups with a significant difference in calcium intake, nutrient adequacy ratio, and nutrient density by region were 14 to 19, 20 to 29, and ≥65 years. Calcium intake and dietary quality were lowest in the low household income group. In terms of being a recipient of the dietary life supply, the calcium intake and dietary quality of the recipient group was low. CONCLUSIONS: We found that daily calcium intake was very different by region and was significantly lower in region with lower SES. The findings of this study suggest social inequalities in calcium intake by region can be addressed in the development and implementation of tailored nutritional interventions to promote calcium nutritional status of Koreans.